Respostas

  • Usuário do Brainly
2014-08-10T03:12:16-03:00
A)
 \frac{6. 10^{-3-4+8} }{6. 10^{-1+4} } = \frac{6.10}{6. 10^{3} } = \frac{1}{ 10^{2} } = \frac{1}{100}

b)
   (2) ^{3} + 2^{5} =8+32=40

c)
   1+( \frac{3+5}{15} ):( \frac{9-1}{y} )=

  1+( \frac{8}{15}):( \frac{8}{15} )=1+1=2

d)
   -2+(-3).(- \frac{1}{2}):(-3)=

   -2+( \frac{3}{2} ).(- \frac{1}{3})=

   -2- \frac{1}{2} = \frac{-4-1}{2} =- \frac{5}{2}

e)
   ( -\frac{5}{3} ) ^{-3} .( \frac{6}{10} ) ^{-2} =

   ( \frac{27}{125} ).( \frac{100}{36} )= \frac{3}{5}

simplifiquei,27 com 36--125 com 100

f)

  2 \sqrt{ 2^{2}.3. 5^{2}  } +3 \sqrt{2. 5^{2} } -2 \sqrt{ 3^{2}. 3^{2} .3 } =

2.2.5 \sqrt{3} +3.5 \sqrt{2} -2.3.3 \sqrt{3} =

  20 \sqrt{3} +15 \sqrt{2} -18 \sqrt{3} =2 \sqrt{3} +15 \sqrt{2}

g)

  \sqrt{13 +\sqrt{7+ \sqrt{2+2} } } =

 \sqrt{13+ \sqrt{7+ \sqrt{4} } } =

 \sqrt{13+ \sqrt{7+2} } =

 \sqrt{13+ \sqrt{9} } =

 \sqrt{13+3}

 \sqrt{16} =4
1 5 1